The Role of Positive Leadership in Improving Employee Psychological Wellbeing in the Assessment Center of PT Bukit Asam Tbk. - Dwi Hurriyati; Aldy Anugrah (Hasanuddin University, 2025)
This study examines the impact of positive leadership on improving employee psychological well-being, particularly in the mining industry work environment. The study uses positive leadership theory and PERMA-V theory as conceptual frameworks to analyze how leadership styles can create a supportive work environment and enhance employee psychological well-being. The research employs a descriptive qualitative method through participatory observation, informal interviews, and literature review in the workplace of the Assessment Center at PT Bukit Asam. The findings reveal that while financial well-being has been achieved, psychological stress levels due to workloads and deadlines remain high. Therefore, the application of positive leadership has proven effective in creating a more supportive work environment, boosting work morale, and strengthening employees' mental health. This study underscores the importance of integrating positive leadership principles into human resource management strategies to achieve holistic employee well-being.